Elevated serum interleukin-38 levels in polymyositis and dermatomyositis: diagnostic implications and correlations with inflammatory markers - Qin, Wen; Li, Zhi; Fu, Guohua; Li, Yan; Huang, Wenyan; Yu, Mengxi; Wu, Xiudi; Li, Mingcai (Frontiers in Immunology, 2026)
BackgroundInterleukin (IL)-38 has been recently identified as an anti-inflammatory cytokine. Polymyositis (PM) and dermatomyositis (DM) are two prevalent clinical inflammatory myopathies. This study aims to investigate the serum concentrations of IL-38 in patients with PM/DM and their association with these conditions.MethodsSerum IL-38 levels were quantified using the enzyme-linked immunosorbent assay method in a cohort of 117 subjects, comprising 77 patients with myositis (8 with PM and 69 with DM) and 40 healthy controls. A comprehensive assessment of preliminary clinical characteristics was conducted for each participant through physical examination and review of medical records. The diagnostic utility of IL-38 in PM/DM was evaluated using the receiver operating characteristic curve.ResultsThe findings revealed that serum IL-38 concentrations were significantly elevated in patients with PM/DM compared to the control group, irrespective of the presence of interstitial lung disease. No significant difference was observed between the PM and DM groups. Furthermore, IL-38 demonstrated a positive correlation with the visual analogue scale, lactate dehydrogenase (LDH), and other inflammatory markers. Finally, IL-38, either independently or in conjunction with LDH, exhibits significant diagnostic potential.ConclusionThe study’s findings reveal that patients with PM/DM who present elevated serum levels of IL-38 also show a positive correlation with LDH levels. This suggests IL-38 may participate in modulating inflammatory immune responses in PM/DM and could serve as a potential candidate indicator for these conditions.